A copper-based composite material with anti-adhesion and anti-fusion welding properties, and preparation method and application thereof

By introducing micron-scale Ti, Si and X metal particles into the copper-based composite and heat treatment, the problems of electrode adhesion and contact fusion welding are solved, which significantly improves the anti-adhesion and fusion welding properties of the material, extends the service life and reduces costs.

CN119736499APending Publication Date: 2025-04-01NORTH CHINA ELECTRIC POWER UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411903056.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing copper-based composite materials are prone to adhere under high temperature, high voltage and high current density conditions, resulting in electrode wear, instability in welding and shortened service life. At the same time, the reliability of contacts after welding is reduced, resulting in environmental pollution, high cost and complex processes.

Method used

Micron-scale Ti, Si and X metal particles were introduced into the copper alloy by melt casting method, and a uniform Cu-Ti-Si-X composite material was prepared and heat treated to improve the performance of the material.

Benefits of technology

It significantly improves the anti-adhesion and anti-welding properties of copper-based composites, extends the service life of electrodes or contacts, improves welding quality and contact reliability, and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736499A_ABST
    Figure CN119736499A_ABST
Patent Text Reader

Abstract

The present invention provides a copper-based composite material with resistance to adhesion and fusion welding, and a preparation method and application thereof, which belong to the field of composite material preparation. The copper-based composite material prepared by the present invention includes the following components: Ti, Si, X and copper, and a micron-sized particle reinforcement phase is introduced into the copper alloy by a melt-casting method to obtain a Cu-Ti-Si-X composite material with uniform structure. The present invention obtains a copper alloy containing a particle reinforcement phase by optimizing the preparation process. The present invention achieves the improvement of the anti-adhesion and anti-fusion welding performance of the composite material when it is used as a resistance welding electrode or an electrical contact by introducing micron-sized particles, effectively prolonging the service life of the electrode or contact, improving the welding quality or the reliability of the contact, and reducing the maintenance cost. The copper-based composite material described in the present invention has broad industrial application prospects in the fields of resistance welding electrodes, electrical contacts, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of copper-based composite materials, and in particular to an anti-adhesion and anti-fusion welding copper-based composite material and a preparation method and application thereof. Background Art

[0002] Electrical contacts, electrodes, etc. play a vital role in various industrial applications, and their performance requirements are getting higher and higher. Taking welding electrodes as an example, with the rapid development of industries such as aerospace, high-speed rail equipment, new energy vehicles and related batteries, the requirements for welding processes are also more complex, which also puts forward higher performance requirements for electrode materials. The main function of the electrode is to conduct current, withstand heat load and maintain good contact with the workpiece under certain conditions. Depending on the application field, the selection of electrode materials usually considers electrical conductivity, thermal conductivity, wear resistance, corrosion resistance and high temperature resistance. When the electrode is used, the problem of electrode adhesion is a common problem, especially under high temperature, high pressure and high current density working conditions. The adhesion phenomenon is usually manifested as melting or adhesion between the electrode material and the workpiece material or other contacting media, which will cause problems such as electrode wear, unstable welding and shortened electrode life. These adhesion phenomena directly affect the working performance, product quality and production efficiency of the equipment, and increase the frequency of maintenance and replacement of electrodes, thereby increasing the operating cost. Corresponding to this is the problem of fusion welding of electrical contacts. After the contact is fusion welded, the breaking capacity of the contact will be reduced and its reliability will be reduced.

[0003] At present, in order to deal with the problems of electrode adhesion and contact anti-welding, many different copper-based composite materials have been developed. For example, CN118455837A discloses a composite material with high strength and high wear resistance prepared by adding trace silver fiber and carbon fiber to Cu-Ni-Be alloy, which can reduce the wear rate of the electrode during use and ensure good performance. In order to further improve the safety and environmental protection of the material, CN118406919A discloses a copper-based composite material reinforced with nano-ceramic particles by adding metals such as Sc and Y to Cu-Cr-Zr alloy, and using hot pressing sintering to prepare the composite material, and the synergistic effect of micron-level metallic glass and submicron-level Sc2O3 is used to make the composite material have better mechanical properties and electrical conductivity. In order to further expand the scope of application, CN115502606A discloses a method for preparing a Cu-αAl2O3 gradient composite electrode, and the pure copper at the tail of the prepared composite material can provide good electrical and thermal conductivity, and the end material is dispersed with a high volume fraction of nano-Al2O3 particles, so that it has excellent resistance welding electrode performance.

[0004] The addition of micronized particles can significantly improve the mechanical properties and wear resistance of copper alloys, making them more valuable for application. Although the existing technology has alleviated the electrode adhesion problem to a certain extent, it still has disadvantages such as environmental pollution, high cost or complex preparation process. In view of the above problems, how to prepare a more economical, sustainable and efficient material to solve or significantly reduce the electrode adhesion problem is still a research and development hotspot in this field. Summary of the invention

[0005] Based on the problems existing in the prior art, the present invention provides a preparation process of a copper-based composite material, which improves its anti-adhesion and anti-welding properties and increases the service life of electrodes or contacts. The preparation process is described below.

[0006] A method for preparing an anti-adhesion and anti-welding copper-based composite material comprises the following steps:

[0007] (1) Weighing pure copper, Ti, Si and X metal raw materials, drying them for later use; the pure copper includes copper foil and copper block;

[0008] (2) Ti, Si and X metal are mixed uniformly to obtain a mixed powder; the mixed powder is then placed in a tablet press and cold pressed into a cylindrical block with a diameter of 20 to 22 mm, and then covered with copper foil for later use;

[0009] (3) placing a Cu block in a graphite crucible and heating it until it is completely melted; then pressing the cylindrical pressed block in step (3) into the molten Cu and keeping the temperature to obtain a Cu melt;

[0010] (4) Deslagging the Cu melt in step (3) and casting to obtain the copper-based composite material.

[0011] Preferably, the X in step (1) includes but is not limited to one or more of Ni, Co, Fe, C, N, and B; the X metal raw material in step (1) is X powder or an alloy of any one or more of Cu, Ti, and Si and X; the Ti, Si, and X metal raw materials in step (1) are powders of 1 to 30 μm.

[0012] Preferably, in step (1), the raw materials are weighed according to the following element ratios: Ti 0.1% to 8.0%, Si 0.1% to 4.0%, X 0.1% to 10% and the balance Cu;

[0013] The drying temperature in step (1) is 90-200°C.

[0014] Preferably, one or more of the X metals in step (2) are individually briquette-formed.

[0015] Preferably, the pressure of the tablet press in step (2) is 5 to 30 MPa.

[0016] Preferably, the heating temperature in step (3) is 1100-1300° C. and the insulation time is 1-5 min.

[0017] Preferably, the slag removal in step (4) is carried out using a slag removal agent, and the slag removal agent is cryolite; the amount of the slag removal agent added is 0.2% to 0.4% of the total mass of the alloy; and the casting temperature in step (5) is 1280 to 1340°C.

[0018] Preferably, the preparation method further comprises a heat treatment step, and the specific method of the heat treatment step is:

[0019] The copper-based composite material in step (5) is subjected to homogenization annealing → hot rolling → solution treatment → cold rolling → aging treatment to finally obtain the desired sample;

[0020] The homogenization annealing temperature is 900-1000°C, and the annealing time is 1-4h; the hot rolling temperature is 900-1000°C, the total hot rolling deformation is 50%-90%, and the final rolling temperature is above 800°C; the solution temperature is 900-1000°C, and the solution time is 1-4h; the total cold rolling deformation is 30%-80%; the aging temperature is 400-500°C, and the aging time is 0.5h-8h.

[0021] The present invention also provides an anti-adhesion and anti-fusion welding copper-based composite material prepared by the above method.

[0022] The copper-based composite material prepared by the invention is used for manufacturing resistance welding electrodes, electric contacts, electrical connectors and vacuum switches.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention introduces a micron-sized particle reinforcement phase into a copper alloy by a melt-casting method to obtain a Cu-Ti-Si-X composite material with a uniform structure. The present invention achieves the improvement of the anti-adhesion and anti-fusion welding properties of the composite material when used as a resistance welding electrode or an electrical contact, effectively prolongs the service life of the electrode or the contact, improves the welding quality or the reliability of the contact, and reduces maintenance costs. The copper-based composite material described in the present invention has broad industrial application prospects in the fields of resistance welding electrodes, electrical contacts, etc. The method of the present invention utilizes the good properties of the particle reinforcement phase itself to effectively prevent material adhesion caused by melting or softening due to local overheating of the electrode surface, and can be used to slow down electrode adhesion or contact fusion welding, thereby improving the performance and service life of the electrode or contact. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The microscopic morphology of the cast Cu-Ti-Si-Ni alloy prepared in Example 1;

[0026] Figure 2 The microscopic morphology of the cast Cu-Ti-Si-Ni-D alloy prepared in Example 2;

[0027] Figure 3 This is a microscopic morphology of the cast Cu-Ti-Si-N alloy prepared in Example 3;

[0028] Figure 4 This is a microscopic morphology of the electrode prepared in Example 1 after use. DETAILED DESCRIPTION

[0029] The present invention provides a method for preparing an anti-adhesion and anti-fusion welding copper-based composite material, the steps of which are as follows:

[0030] (1) Weighing pure copper, Ti, Si and X metal raw materials, drying them for later use; the pure copper includes copper foil and copper block;

[0031] (2) Ti, Si and X metal are mixed uniformly to obtain a mixed powder; the mixed powder is then placed in a tablet press and cold pressed into a cylindrical block with a diameter of 20 to 22 mm, and then covered with copper foil for later use;

[0032] (3) placing a Cu block in a graphite crucible and heating it until it is completely melted; then pressing the cylindrical pressed block in step (3) into the molten Cu and keeping the temperature to obtain a Cu melt;

[0033] (4) Deslagging the Cu melt in step (3) and casting to obtain the copper-based composite material.

[0034] Preferably, the X in step (1) includes but is not limited to one or more of Ni, Co, Fe, C, N, and B; the X metal is X powder or an alloy of any one or more of Cu, Ti, and Si and X;

[0035] The Ti, Si and X metal raw materials in step (1) are powders of 1 to 30 μm. In a specific embodiment of the present invention, the raw material powders include any one or more of the following components: 30 μm Ti powder, 10 μm Si powder, 10 μm Ni powder, 5 μm graphite powder, 10 μm diamond powder, 5 μm SiC powder, and 3 μm Si3N4 powder.

[0036] Preferably, the raw materials in step (1) are weighed according to the following element ratios: Ti 0.1% to 8.0%, Si 0.1% to 4.0%, X 0.1% to 10% and the balance Cu.

[0037] Preferably, the drying temperature in step (1) is 90-200°C.

[0038] Preferably, the mixing time in step (2) is 1 to 6 hours.

[0039] Preferably, the pressure of the tablet press in step (2) is 5 to 30 MPa;

[0040] Preferably, the X powder in step (2) can be individually briquette-pressed as required.

[0041] Preferably, the heating temperature in step (3) is 1100-1300° C.; the holding time is 1-5 min;

[0042] The cylindrical compact in step (3) is pressed into the bottom of the molten Cu.

[0043] Preferably, the slag removal agent used in step (4) is cryolite, and the amount of the slag removal agent added is 0.2% to 0.4% of the total mass of the alloy; the casting temperature in step (4) is 1280 to 1340°C.

[0044] Preferably, the preparation method further comprises a heat treatment step, and the specific method of the heat treatment step is:

[0045] The copper-based composite material in step (4) is subjected to homogenization annealing → hot rolling → solution treatment → cold rolling → aging treatment to finally obtain the desired sample;

[0046] The homogenization annealing temperature is 900-1000°C, and the annealing time is 1-4h; the hot rolling temperature is 900-1000°C, the total hot rolling deformation is 50%-90%, and the final rolling temperature is above 800°C; the solution temperature is 900-1000°C, and the solution time is 1-4h; the total cold rolling deformation is 30%-80%; the aging temperature is 400-500°C, and the aging time is 0.5h-8h.

[0047] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0048] Example 1

[0049] A method for preparing an anti-adhesion and anti-welding copper-based composite material, comprising the following steps:

[0050] (1) Weighing pure copper, and then placing 1.2% Ti powder, 1.3% Si powder and 6% Ni powder in a drying oven at 90° C. for later use; the pure copper includes copper foil and copper block;

[0051] (2) Ti powder and Si powder are placed in a three-dimensional oscillating mixer for 3 hours to obtain a mixed powder; the mixed powder is then placed in a tablet press and cold-pressed at 10 MPa into a cylindrical block with a diameter of 20 mm. Ni powder is pressed separately, and then the cylindrical block is coated with a 0.2 mm copper foil to ensure that the morphology of the block is not damaged and set aside;

[0052] (3) placing a Cu block in a graphite crucible and heating it to 1250° C. to completely melt it; then pressing the cylindrical compact in step (2) into the molten Cu, keeping the temperature for 2 min, and adding Ni powder to the compact to obtain a Cu melt;

[0053] (4) adding 0.3% cryolite by weight of the alloy to the Cu melt in step (3) for slag removal, and casting at 1320° C. to obtain the copper-based composite material;

[0054] (5) subjecting the alloy to homogenization annealing → hot rolling → solution treatment → water cooling quenching → cold rolling → aging treatment, and finally obtaining a Cu-Ti-Si-Ni alloy;

[0055] The homogenization annealing temperature is 950°C, and the annealing time is 3h; the hot rolling temperature is 950°C, the total hot rolling deformation is 90%, and the final rolling temperature is 850°C; the solution temperature is 980°C, and the solution time is 1h; the total cold rolling deformation is 60%; the aging temperature is 475°C, and the aging time is 0.5h.

[0056] The composition of the composite material and the mass percentage of each element are: Ti 1.2%, Si 1.3%, Ni 6% and the balance Cu. The microscopic morphology of the cast Cu-Ti-Si-Ni alloy is shown in FIG. Figure 1 .

[0057] Example 2

[0058] A method for preparing an anti-adhesion and anti-welding copper-based composite material, the steps are as follows:

[0059] (1) Weighing pure copper, and then placing 1.8% Ti powder, 0.85% Si powder, 1% diamond powder and 3.57% Ni powder in a drying oven at 110° C. for use; the pure copper includes copper foil and copper block;

[0060] (2) Ti powder, Si powder and diamond powder are placed in a three-dimensional oscillating mixer for mixing for 3 hours to obtain a mixed powder; the mixed powder is then placed in a tablet press and cold-pressed at 15 MPa into a cylindrical compact with a diameter of 20 mm, Ni powder is pressed separately, and then the cylindrical compact is coated with a 0.2 mm copper foil to ensure that the compact morphology is not damaged and set aside;

[0061] (3) placing a Cu block in a graphite crucible and heating it to 1250° C. to completely melt it; then pressing the cylindrical compact in step (2) into the molten Cu, keeping the temperature for 2 min, and adding Ni powder to the compact to obtain a Cu melt;

[0062] (4) adding 0.3% cryolite by weight of the alloy to the Cu melt in step (3) for slag removal, and casting at 1300° C. to obtain the copper-based composite material;

[0063] (5) subjecting the alloy to homogenization annealing → hot rolling → solution treatment → water cooling quenching → cold rolling → aging treatment, and finally obtaining a Cu-Ti-Si-Ni-D alloy;

[0064] The homogenization annealing temperature is 1000°C, and the annealing time is 1h; the hot rolling temperature is 950°C, the total hot rolling deformation is 85%, and the final rolling temperature is 900°C; the solution temperature is 900°C, and the solution time is 1h; the total cold rolling deformation is 50%; the aging temperature is 475°C, and the aging time is 6h.

[0065] The composition and mass percentage of each element of the composite material are: Ti 1.8%, Si 0.85%, Ni 3.57%, diamond 1% and the balance Cu. The microscopic morphology of the cast Cu-Ti-Si-Ni-D alloy is shown in FIG. Figure 2 .

[0066] Example 3

[0067] A method for preparing an anti-adhesion and anti-welding copper-based composite material, the steps are as follows:

[0068] (1) Weighing pure copper, and then placing 6.2% Ti powder, 0.1% Si powder and 1.8% Si3N4 powder in a drying oven at 90° C. for later use; the pure copper includes copper foil and copper block;

[0069] (2) Ti powder, Si powder and Si3N4 powder are placed in a three-dimensional oscillating mixer for 4 hours to obtain a mixed powder; the mixed powder is then placed in a tablet press and cold-pressed at 10 MPa into a cylindrical compact with a diameter of 20 mm, and then the cylindrical compact is coated with a 0.2 mm copper foil to ensure that the compact morphology is not damaged and set aside;

[0070] (3) placing a Cu block in a graphite crucible and heating it to 1300° C. to completely melt it; then pressing the cylindrical pressed block in step (2) into the molten Cu and keeping the temperature for 1 minute to obtain a Cu melt;

[0071] (4) 0.4% cryolite by weight of the alloy is added to the Cu melt in step (3) for slag removal, and the copper-based composite material is obtained by casting at 1290° C., which is recorded as Cu-Ti-Si-N alloy.

[0072] The composition and mass percentage of each element of the composite material are: Ti 6.2%, Si 0.1%, Si3N4 1.8% and the balance Cu. The microscopic morphology of the cast Cu-Ti-Si-N alloy is shown in FIG. Figure 3 .

[0073] The performance comparison results of the composite materials in Examples 1 to 3 are shown in Table 1. It can be seen from Table 1 that the introduction of the particle reinforcement phase can effectively increase the strength, conductivity and softening temperature of the material while ensuring that the alloy hardness meets the application requirements, thereby improving its anti-adhesion performance.

[0074] Table 1

[0075]

[0076] The copper-based composite material prepared in Example 1 was used as an electrode of a gold-tin alloy plate. The welding environment was room temperature 25°C, the welding current was 800A, the single-point welding duration was 20ms, the welding pressure was 3.0MPa, and the pressure was maintained for 1s after each welding point to ensure the cooling of the molten core. The above operation was repeated until the electrode needed to be ground. At this time, the microscopic morphology of the electrode was as follows: Figure 4 .from Figure 4 It can be seen that there is no adhesion on the surface of the composite contact after being used as an electrode.

[0077] It should be noted that the above are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and other variations are possible. All variations directly or indirectly derived from the disclosure of the present invention by those skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A method for preparing an anti-adhesion and anti-welding copper-based composite material, characterized in that: The following steps are involved: (1) Weighing pure copper, Ti, Si and X metal raw materials, drying them for later use; the pure copper includes copper foil and copper block; (2) Ti, Si and X metal are mixed uniformly to obtain a mixed powder; the mixed powder is then placed in a tablet press and cold pressed into a cylindrical block with a diameter of 20 to 22 mm, and then covered with copper foil for later use; (3) placing a Cu block in a graphite crucible and heating it until it is completely melted; then pressing the cylindrical pressed block in step (3) into the molten Cu and keeping the temperature to obtain a Cu melt; (4) Deslagging the Cu melt in step (3) and casting to obtain the copper-based composite material.

2. The method for preparing the anti-adhesion and anti-welding copper-based composite material according to claim 1, characterized in that: The X in step (1) includes but is not limited to one or more of Ni, Co, Fe, C, N, and B. The X metal in step (1) is X powder or an alloy of any one or more of Cu, Ti, and Si and X. The Ti, Si, and X metal raw materials in step (1) are powders of 1 to 30 μm.

3. The method for preparing the anti-adhesion and anti-welding copper-based composite material according to claim 1, characterized in that: In step (1), the raw materials are weighed according to the following element ratios: Ti 0.1% to 8.0%, Si 0.1% to 4.0%, X 0.1% to 10% and the balance Cu; The drying temperature in step (1) is 90-200°C.

4. The method for preparing the anti-adhesion and anti-welding copper-based composite material according to claim 1, characterized in that: In the step (2), one or more of the X metals are individually briquette-pressed.

5. The method for preparing the anti-adhesion and anti-welding copper-based composite material according to claim 1, characterized in that: The pressure of the tablet press in step (2) is 5 to 30 MPa.

6. The method for preparing the anti-adhesion and anti-welding copper-based composite material according to claim 1, characterized in that: The heating temperature in step (3) is 1100-1300° C.; the insulation time is 1-5 minutes.

7. The method for preparing the anti-adhesion and anti-welding copper-based composite material according to claim 1, characterized in that: The slag removal in step (4) is carried out using a slag removal agent, the slag removal agent is cryolite, and the amount of the slag removal agent added is 0.2% to 0.4% of the total mass of the alloy; the casting temperature in step (4) is 1280 to 1340°C.

8. The method for preparing the anti-adhesion and anti-welding copper-based composite material according to claim 1, characterized in that: The preparation method further comprises a heat treatment step, and the specific method of the heat treatment step is: The copper-based composite material in step (4) is subjected to homogenization annealing → hot rolling → solution treatment → cold rolling → aging treatment to finally obtain the desired sample.

9. A copper-based composite material with anti-adhesion and anti-welding properties, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

10. The use of the anti-adhesion and anti-welding copper-based composite material according to claim 9, characterized in that: The copper-based composite material is used for manufacturing resistance welding electrodes, electric contacts, electrical connectors and vacuum switches.

Citation Information

Patent Citations

  • Preparation method of Cu / alpha-Al2O3 gradient composite electrode for electric resistance welding

    CN115502606A

  • Copper alloy composite material and preparation method and application thereof

    CN118406919A

  • Beryllium-nickel-copper for resistance welding electrode and preparation method of beryllium-nickel-copper

    CN118455837A